Increased Transnational Sea Ice Transport Between Neighboring Arctic States in the 21st Century. Issue 3 (22nd March 2020) - DeRepentigny, Patricia; Jahn, Alexandra; Tremblay, L. Bruno; Newton, Robert; Pfirman, Stephanie
Abstract: The Arctic is undergoing a rapid transition toward a seasonal ice regime, with widespread implications for the polar ecosystem, human activities, as well as the global climate. Here we focus on how the changing ice cover impacts transborder exchange of sea ice between the exclusive economic zones of the Arctic states. We use the Sea Ice Tracking Utility, which follows ice floes from formation to melt, in conjunction with output diagnostics from two ensembles of the Community Earth System Model that follow different future emissions scenarios. The Community Earth System Model projects that by midcentury, transnational ice exchange will more than triple, with the largest increase in the amount of transnational ice originating from Russia and the Central Arctic. However, long‐distance ice transport pathways are predicted to diminish in favor of ice exchanged between neighboring countries. By the end of the 21st century, we see a large difference between the two future emissions scenarios considered: Consistent nearly ice‐free summers under the high emissions scenario act to reduce the total fraction of transnational ice exchange compared to midcentury, whereas the low emissions scenario continues to see an increase in the proportion of transnational ice. Under both scenarios, transit times are predicted to decrease to less than 2 yr by 2100, compared to a maximum of 6 yr under present‐day conditions and 2.5 yr by midcentury. These significant changes in ice exchange and transit time raise important concerns regarding risks associated with ice‐rafted contaminants. Plain Language Summary: The Arctic is undergoing a rapid transition toward a thinner, less extensive, more mobile sea ice cover. This affects the amount of sea ice exchanged between the exclusive economic zones of Arctic states. Here we use an Earth System Model, the Community Earth System Model, to track sea ice from where it forms to where it ultimately melts. By midcentury, the area of sea ice exchanged between the different regions of the Arctic is predicted to more than triple compared to the end of the twentieth century, with the Central Arctic joining Russia as a major ice "exporter." At the same time, the exchange of sea ice over long distances is predicted to diminish in favor of ice exchanged between neighboring Arctic states. By midcentury, the average time required for ice to travel from one region to another is more than halved; by 2100, nearly all transports take less than a year, with little multiyear ice left in the Arctic. Sea ice provides a transport mechanism for a variety of material, including algae, dust, and a range of pollutants. The acceleration, and then disappearance, of sea ice has important implications for managing contamination in Arctic waters. Key Points: The CESM projects a large increase in transnational ice exchanged in the Arctic by midcentury with transit times reduced to under 2 yr By midcentury the amount of transnational ice originating from Russia doubles and the Central Arctic emerges as the second dominant source Long‐distance ice transport pathways diminish by 2100 in favor of regions directly downstream, especially under the high emissions scenario